Development of "Futsal Kids" Game Model to Improve Elementary School Students Motor Skills - Alfairuzzabady, Alfairuzzabady; Kristina, Putri Cicilia; Putri, Siti Ayu Risma (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2025)
This study aims to develop and test the effectiveness of the "Futsal Kids" game model as an innovation in futsal training for extracurricular activities to increase students' motor skills. School-based research using the research and development (R&D) method, with the Borg & Gall steps simplified and experimental. One-Group Pretest–Posttest Design. The subject study is a student-based class above who participate in futsal extracurricular activities at three schools in Palembang City, with 25 students in the trial, 50 students in the trial field, and 50 students who tested the effectiveness. Instrument study covering observation, questionnaires, interviews, and testing basic motor skills (coordination, agility, speed, balance, and control). Validation results from three experts show that the "Futsal Kids" game model obtained an average eligibility rating of 89.2% with the "worthy" category. The trial, limited and field show that the model is easy to apply, tailored to students' characteristics, and receives very positive responses from teachers and students. Results of the effectiveness test show an average score increase in motor skills from 67.74 (pretest) to 82.20 (posttest) with a p-value < 0.05. The most significant increase occurs in control movement (23.6%) and agility (22.3%). Thus, the game model "Futsal Kids" is deemed feasible, practical, and effective for increasing students' motor skills through school-based futsal training and fun, educational games.